2010
DOI: 10.1523/jneurosci.6421-09.2010
|View full text |Cite
|
Sign up to set email alerts
|

Sertad1 Plays an Essential Role in Developmentaland Pathological Neuron Death

Abstract: Developmental and pathological death of neurons requires activation of a defined pathway of cell cycle proteins. However, it is unclear how this pathway is regulated and whether it is relevant in vivo. A screen for transcripts robustly induced in cultured neurons by DNA damage identified Sertad1, a Cdk4 (cyclin-dependent kinase 4) activator. Sertad1 is also induced in neurons by nerve growth factor (NGF) deprivation and A␤ (␤-amyloid). RNA interference-mediated downregulation of Sertad1 protects neurons in all… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 50 publications
1
18
0
Order By: Relevance
“…Rat-shParkin was generated in pSIREN vector based on the following target sequence: 5′-ATCACCTGACAGTACAGAACT -3′. Two control shRNA constructs were used: for transfection experiments, a mutant version of GATA2 silencing target sequence (Biswas et al, 2010), with no detectable homology to rodent genomic sequence, was used: 5′-GCACCTGATGTCTTCTTCAACC-3′; for lentiviral experiments, we used a mutated version of shATF4-A (mutated bases are underlined): 5′-GCC A GA T TC A GC G GC C TA C AT-3′. Rat and human ATF4 cDNAs were cloned into pCMS-eGFP, which co-expresses eGFP, for single transfection experiments, or into pcDNA3.1 for co-transfection experiments.…”
Section: Methodsmentioning
confidence: 99%
“…Rat-shParkin was generated in pSIREN vector based on the following target sequence: 5′-ATCACCTGACAGTACAGAACT -3′. Two control shRNA constructs were used: for transfection experiments, a mutant version of GATA2 silencing target sequence (Biswas et al, 2010), with no detectable homology to rodent genomic sequence, was used: 5′-GCACCTGATGTCTTCTTCAACC-3′; for lentiviral experiments, we used a mutated version of shATF4-A (mutated bases are underlined): 5′-GCC A GA T TC A GC G GC C TA C AT-3′. Rat and human ATF4 cDNAs were cloned into pCMS-eGFP, which co-expresses eGFP, for single transfection experiments, or into pcDNA3.1 for co-transfection experiments.…”
Section: Methodsmentioning
confidence: 99%
“…In utero electroporation was as described in Biswas et al, 2010 except that DNA (2μg/1μl) was injected through the dorsal mesencephalon rather than telencephalon. Due to the thin lateral dimension of the mesencephalic ventricle, the capillary syringe was placed through the dorsal midline angled in the direction of the cephalic flexure.…”
Section: Methodsmentioning
confidence: 99%
“…Cortical neurons are severely affected in AD brains and undergo death after exposure to oligomeric A␤ in vitro (5,26,28,29,(37)(38)(39). We have recently shown that the oligomeric A␤(1-42) at a concentration of 1.5 M induced significant neuron death after 24 h. Neuron death first becomes apparent by 12-16 h of A␤ exposure, and more than 40% of neurons die within 24 h (4).…”
Section: Puma Is Induced In Neurons In Response To A␤ In Cultures and Inmentioning
confidence: 99%